2014
DOI: 10.1111/lam.12300
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading the antioxidant potential of cereals by their fungal fermentation under solid-state cultivation conditions

Abstract: Antioxidant-rich food products are getting popularity day by day. In this study, potential of solid-state fermentation (SSF) has been studied for the improvement of antioxidant potential of different cereals by GRAS micro-organisms. The comparative evaluation of the antioxidant potential of various fungal fermented products derived from whole grain cereals, such as wheat, brown rice, oat and maize, has been carried out. Among these, Rhizopus oryzae RCK2012-fermented wheat was observed as a potent source of nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 31 publications
(58 reference statements)
1
29
0
1
Order By: Relevance
“…It was noted SSF with C. militaris significantly (P < 0.05) enhanced the antioxidant activity of red beans regardless of the different extraction solvents used. (Cheng et al 2013), chickpea fermented with C. militaris (Xiao et al 2014), and cereals (wheat, maize, and oats) fermented with A. oryzae and A. awamori (Bhanja Dey and Kuhad 2014). SSF with microbe enhanced antioxidant activity compared with the nonfermented products; similar results were also found in black soybean fermented with Rhizopus spp.…”
Section: Resultsmentioning
confidence: 52%
“…It was noted SSF with C. militaris significantly (P < 0.05) enhanced the antioxidant activity of red beans regardless of the different extraction solvents used. (Cheng et al 2013), chickpea fermented with C. militaris (Xiao et al 2014), and cereals (wheat, maize, and oats) fermented with A. oryzae and A. awamori (Bhanja Dey and Kuhad 2014). SSF with microbe enhanced antioxidant activity compared with the nonfermented products; similar results were also found in black soybean fermented with Rhizopus spp.…”
Section: Resultsmentioning
confidence: 52%
“…The effect of fermentation on the bioactive and physicochemical properties of cereal grains by Lactobacillus, Bacillus, Rhizopus or Aspergillus had been investigated previously (Bhanja Dey & Kuhad, 2014a;2014b;Ðordević et al, 2010;Sanjukta, Rai, Muhammed, Jeyaram, & Talukdar, 2015;Schmidt et al, 2014;Wang, Wu, & Shyu, 2014). However, the influence of SSF with C. militaris on the antioxidant activity and antioxidant compounds of oats has received little attention.…”
Section: Introductionmentioning
confidence: 97%
“…BhanjaDey and Kuhad (2014) reported that the TPC of cereal samples fermented with Aspergillus awamori and Aspergillus oryzae significantly increased compared with that of non-fermented samples.Singh et al (2010) also demonstrated that TPC of soybean improved by SSF with Trichoderma harzianum, possibly because the enzyme of the fungus plays an important role in the mobilization of polyphenolic compounds during fermentation. Previous studies reported that phenolic compounds are present as simple soluble-free esters and, to a greater extent, as complex insoluble bound esters with polysaccharides, proteins, or cell walls in plant materials(Đorđević et al, 2010;Razak et al, 2015; Wang et al, 2014).…”
mentioning
confidence: 99%
“…demonstrated that maize by SSF with the fungus Thamnidium elegans for 5 days significantly (p < 0.05) enhances ABTS· + scavenging activity. BhanjaDey and Kuhad (2014) reported the enhancement of ABTS· + scavenging activity by SSF with A. oryzae,A. awamori, or Rhizopus oryzae, and …”
mentioning
confidence: 99%
See 1 more Smart Citation